PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN ASING SEBAGAI VARIABEL PEMODERASI - Dwija Putra, AA Gde Trisna; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2017)
This study aimed to determine the effect of corporate social responsibility to corporate value disclousure with foreign ownership as moderating variable on Mining Company listed on the Indonesia Stock Exchange 2011-2013. The study design used is associative. This study population is a collection of all mining companies listed on the Stock Exchange over the period 2011-2013 is 40 companies. For the determination of the sample using the method of non-probability sampling, ie sampling technique with a certain considerations. Data were collected to make use of non-participant observation method. The data has been analyzed using analytical techniques moderated regression analysis. The results of this study found that 1) The first hypothesis is proven Corporate Social Responsibility does not affect the value of the company, 2) The second hypothesis is proven to Foreign Ownership moderate the relationship CSR on the value of the company.
Keywords: foreign ownership, corporate values, corporate social responsibility.